What can pottery tell us? – connecting the past through ceramic sherds - Miloglav, Ina (2014)
Ceramic vessels, as all other products which are a part of human activity, reveal a social context of man in the past – his behaviour and activities as well as the social, economic and political conditioning of those activities. The paper presents methodological framework which includes interpreting the lifecycle of a ceramic vessel in as much detail as possible – from choice of material, through shaping and treatment of the surface, to its use and final discarding in the archaeological environment.
ENG